Prosumers in the tourism market: the characteristics and determinants of their behaviour - NIEZGODA, Agnieszka (Economics and Business Review, 2013)
The goal of this article is to characterise the prosumer as a specific consumer category in the tourist market. The author presents the general characteristics of a prosumer and how his/her behaviour is conditioned as a result of general social trends as well as specific features of the tourist market. In order to empirically illustrate the issues involved the author presents results of a direct survey conducted with 3 representatives of various types of tourist companies (a tour operator, a travel agent, an airline representative). The interviewees noted their customers’ intensifi ed activity. While customers have greater expectations and requirements, their knowledge does not translate into cooperation with tourist agencies. The respondents claimed that the new customers interested in new forms of the product included primarily young people as well as business people acquainted with new technologies.